Downtown Revitalisation and Delta Blues in Clarksdale, Mississippi Lessons for Small Cities and Towns - Henshall, John C. (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This book is about Clarksdale, a small town in Mississippi, USA, and how the local community has revitalised the long-dilapidated downtown, with the renewal based on the town's intimate association with Blues music and the culture that flows through the Mississippi Delta. John Henshall highlights underlying trends in downtown decline and revitalisation in cities and towns in America, together with commentary of his own experience at home in Australia. In Clarksdale, downtown economic revitalisation gained momentum in the mid-2000s as local residents and newcomers focused their entrepreneurial and creative efforts on promoting Clarksdale's heritage, which is steeped in Blues music and Delta culture. While much attention to date has been given to large cities - from Sydney to San Francisco and from London to New York - as 'creative cities', little has been written about creativity in small cities and towns. This book delves into the positive role played by creative individuals in the economic revitalisation of downtown Clarksdale. The role of urban planning and community interaction is examined, and key lessons are provided for other small cities and towns, as they seek out opportunities to revitalise their downtowns and town centres.